Social Cultural Approach in the Era of Civil Society 5.0 Based on Pancasila Values as an Effort to Form Students with BerAKHLAK (Academically Oriented, Humanist, Liability, Adaptive and Competitive) in Semarang - Irawan - Malebra; Umar - Farouk; Sumanto - Sumanto (JOBS (Jurnal Of Business Studies), 2023)
This research is to be able to reveal the real conditions faced by students on several campuses in Tembalang Semarang. Related to the internalisation of Pancasila values as an effort to shape the character of students who are BerAKHLAK (Academically Oriented, Humanist, Liability, Adaptive, and Competitive). To apply the values of Pancasila, there needs to be strategic steps both formal and non-formal education in order to holistically internalise the value of the Pancasila precepts. With the hope that Pancasila and Citizenship (Character Building) education is oriented towards the development of soft skills BerAKHLAK (Academically Oriented, Humanist, Liability, Adaptive, and Competitive).  The basis of qualitative research is constructivism which assumes that reality is multi-dimensional, interactive, and an exchange of social experiences interpreted by each individual. Qualitative research is descriptive analytical. The results of data analysis are in the form of a description of the situation under study which is presented in the form of a narrative description. Respondents of this study consisted of students who had been able to material/classes of Pancasila and Citizenship with a population of students on state campuses around tembalang including Diponegoro University, Politeknik Negeri Semarang, and Politeknik Kesehatan Semarang. With the number of respondents 20 students. This research is expected to contribute thoughts and recommendations to the special authorised institution, namely the Pancasila Ideology Development Agency (BPIP) and contribute ideas and ideas for the Pancasila and Citizenship Education curriculum in Higher Education in particular. Superior Human Resources to welcome the demographic bonus, will be a great capital for the Golden Indonesia 2045.